Implementation of Good Governance in Reporting Financial Accountability Letter of Bawaslu North Sumatra - Sihombing, Novaria; Nina Siti Salmaniah Siregar,; M. Arif Nasution, (Jurisprudentie : Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2025)
This study aims to analyze the implementation of the principles of good governance in the reporting of the 2024 Election Financial Accountability Letter (SPJ) by the Election Supervisory Agency (Bawaslu) of North Sumatra Province. The main focus of the study includes the extent to which the principles of transparency, accountability, participation, responsiveness, effectiveness, efficiency, and rule of law have been applied in the SPJ reporting process. This research uses a descriptive qualitative approach with a case study method, data collection is carried out through in-depth interviews, documentation, and observation of reporting practices in the Bawaslu environment. The results showed that Bawaslu North Sumatra Province has tried to meet good governance standards, especially in the aspects of accountability and transparency through the use of a digital reporting system and the preparation of documents in accordance with the provisions. However, there are still some obstacles such as limited human resources, lack of technical training, and suboptimal public participation. This research recommends strengthening technical regulations, increasing human resource capacity, and involving civil society as strategies to strengthen accountability and transparency in the financial management of future elections.